Phase-Diagram Observation of Liquid-Liquid Phase Separation in the Poly(l-lysine)/ATP System and a Proposal for Diagram-Based Application Strategy - Nobeyama, Tomohiro (Langmuir : the ACS journal of surfaces and colloids, 2023)
Liquid-liquid phase separation (LLPS) is essential to understanding the biomacromolecule compartmentalization in living cells and to developing soft-matter structures for chemical reactions and drug delivery systems. However, the importance of detailed experimental phase diagrams of modern LLPS systems tends to be overlooked in recent times. Even for the poly(l-lysine) (PLL)/ATP system, which is one of the most widely used LLPS models, any detailed phase diagram of LLPS has not been reported. Herein, we report the first phase diagram of the PLL/ATP system and demonstrate the feasibility of phase-diagram-based research design for understanding the physical properties of LLPS systems and realizing biophysical and medical applications. We established an experimentally handy model for the droplet formation-disappearance process by generating a concentration gradient in a chamber for extracting a suitable condition on the phase diagram, including the two-phase droplet region. As a proof of concept of pharmaceutical application, we added a human immunoglobulin G (IgG) solution to the PLL/ATP system. Using the knowledge from the phase diagram, we realized the formation of IgG/PLL droplets in a pharmaceutically required IgG concentration of ca. 10 mg/mL. Thus, this study provides guidance for using the phase diagram to analyze and utilize LLPS